Optimizing neighborhood park enclosures for pedestrian mobility: A space syntax case study in northern Riyadh - Hosam Salah El Samaty (Ain Shams Engineering Journal, 2025)
Emerging efforts in Saudi Arabia focus on humanizing parks and open spaces in line with Vision 2030. Academics emphasize their role in enhancing well-being and social engagement, yet there is a lack of studies that integrate spatial and statistical methods examining how neighborhood parks’ spatial characteristics integrate with their surrounding urban contexts. This study explores how different enclosure types—fully enclosed, semi-enclosed, and fully open—affect spatial dynamics and movement patterns in adjacent urban areas. Using Space Syntax methodology and statistical modeling, an axial map analysis was conducted for the three enclosure types, evaluating integration, choice, connectivity, and intelligibility within a prototype neighborhood park in northern Riyadh. Findings indicate that semi-enclosed parks enhance integration by regulating accessibility, while fully enclosed parks isolate the park, limiting interaction. Fully open parks promote access but weaken spatial structure. The study provides recommendations for KSA urban developers and highlights the need for further spatial analysis.